2024
DOI: 10.1186/s12936-024-04989-w
|View full text |Cite
|
Sign up to set email alerts
|

Physical and insecticidal durability of Interceptor®, Interceptor® G2, and PermaNet® 3.0 insecticide-treated nets in Burkina Faso: results of durability monitoring in three sites from 2019 to 2022

Jacky Raharinjatovo,
Roch Kounbobr Dabiré,
Keith Esch
et al.

Abstract: Background National Malaria Programmes (NMPs) monitor the durability of insecticide-treated nets (ITNs) to inform procurement and replacement decisions. This is crucial for new dual active ingredients (AI) ITNs, for which less data is available. Pyrethroid-only ITN (Interceptor®) and dual AI (Interceptor® G2, and PermaNet® 3.0) ITNs were assessed across three health districts over 36 months in southern Burkina Faso to estimate median ITN survival, insecticidal efficacy, and to identify factors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…This can be explained by the higher loss rate of the non-pyrethroid active ingredients from the dual AI nets relative to the pyrethroid AI. Studies have also shown a signi cantly higher loss of PBO (> 80%) compared to pyrethroids on pyrethroid-PBO ITNs as they age under operational conditions [28, 29,30]. This suggests that pyrethroids are generally more durable on ITNs than non-pyrethroid compounds used on existing dual AI nets.…”
Section: Discussionmentioning
confidence: 99%
“…This can be explained by the higher loss rate of the non-pyrethroid active ingredients from the dual AI nets relative to the pyrethroid AI. Studies have also shown a signi cantly higher loss of PBO (> 80%) compared to pyrethroids on pyrethroid-PBO ITNs as they age under operational conditions [28, 29,30]. This suggests that pyrethroids are generally more durable on ITNs than non-pyrethroid compounds used on existing dual AI nets.…”
Section: Discussionmentioning
confidence: 99%